ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI BUBUK KOPI DI KOTA PEKANBARU - Gultom Valentin; Harahap Azwar; Mardiana Mardiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research was conducted in Pekanbaru City. The purpose of this study was to determine the factors that influence production in the coffee powder industry in Pekanbaru City. The data used in this study are secondary data and primary data. The analytical method used in this research is quantitative descriptive through the analysis method of Cobb Douglas Production Function with the tool hitng using the SPSS application version 23.0. The variables used are capital, raw materials, and labor in the coffee powder industry in Pekanbaru City. The results of this study indicate that the variables of capital, raw materials, and labor simultaneously together have a significant effect on coffee powder production in Pekanbaru City. Partial regression test (t test) showed that the capital variable with the value of t hitug (2.30)> t table (2.069) with a significant value (0.030) <(0.05), raw material variable with the value of t arithmetic (18,934)> t table (2,069) with significant (0,000) <(0,05) and labor variable with t value (1,431) (0.05) meaning variable capital, and materials standard, positive and significant effect while the labor variable has a positive and not significant effect on the production of the coffee powder industry in Pekanbaru City. Based on the calculation of the coefficient of determination (R2) in proleh of 0.969. This means that 96.9% of the size of coffee powder production in Pekanbaru City is influenced by three independent variables, namely capital, raw materials, and labor. While the remaining 3.1% is influenced by other variables not discussed in this study.Keywords : Coffee Powder Production, Capital, Raw Materials, Labor, CobbDouglas, Spss Version 23.0